If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + x) = x + 5 (1 * 3 + x * 3) = x + 5 (3 + 3x) = x + 5 Reorder the terms: 3 + 3x = 5 + x Solving 3 + 3x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 3x + -1x = 5 + x + -1x Combine like terms: 3x + -1x = 2x 3 + 2x = 5 + x + -1x Combine like terms: x + -1x = 0 3 + 2x = 5 + 0 3 + 2x = 5 Add '-3' to each side of the equation. 3 + -3 + 2x = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 5 + -3 2x = 5 + -3 Combine like terms: 5 + -3 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 2b-b=11 | | 16m-12=12+4 | | sin(4x)=-1 | | x^2+27-12x=0 | | -2x+8=7x-3 | | 2d-d=9 | | w=3a+5n | | 2/3k=12/20 | | 5n-2-7n=2 | | 6z-6=3z | | 7g-5g=20 | | 96+2w=2(80-3w) | | 0.14x+0.6(x-4)=0.01(4x-4) | | j+9j=20 | | 13p+19=-98 | | y-50=-17/3(x-10) | | 3y=4y+3-6 | | x+5=x+29 | | 35x^2-24x+4=0 | | 4y=10-1sobrex | | 2x+3=3x+7 | | -7d=-63 | | 4/5m=9/10 | | 25x+15=17x+6 | | x^3-7x^2+5x-9=0 | | 6(t/3+t/6)=(6)1 | | 9p-4p=20 | | 15+5(5+x)=415 | | 2y^2-y-15= | | 1/4-1/5(y-1)=5y | | 4/5m=9/1 | | 25x+15=17+1 |